O znaczeniu badań ilościowo-jakościowych w edukacji. Próba łączenia wody z ogniem… - Trusz, Sławomir (Studia Edukacyjne, 2017)
Trusz Sławomir, O znaczeniu badań ilościowo-jakościowych w edukacji1. Próba łączenia wody z ogniem… [The Meaning of Mixed Quantitative and Qualitative Research in Education. An Attempt to Combine Fire and Water]. Studia Edukacyjne nr 44, 2017, Poznań 2017, pp. 93-104. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2017.44.6 Social research, including educational studies, could be conducted in accordance with ontological and epistemological assumptions of quantitative vs. qualitative research orientations. When such a distinction is present, the same phenomena are analyzed and presented in a significantly different and often mutually excluding way. Is such an approach justified? It seems it is not. Based on the precedence of a research subject over the method, it could be said that a more comprehensive picture of the phenomena analyzed emerges when researchers make use of methods accepted in both quantitative and qualitative research orientations. The article presents theoretical assumptions and interesting practical solutions of a mixed approach (a mixed methodology) in social research. On the one hand, solutions and methods recommended for the quantitative research can be useful for studies conducted in accordance with the assumptions of qualitative orientation, and on the other hand, solutions and methods recommended for the qualitative research may be useful for the studies conducted in accordance with the assumptions of quantitative orientation. Both approaches have been illustrated by particular examples of research practices.